First record of the South American sailfin catfish Pterygoplichthys multiradiatus in Bangladesh - Hossain, Md. Yeamin; Rahman, Mohammad Mustafizur; Ahmed, Zoarder Faruque; Ohtomi, Jun; Islam, A. B M S (Wiley-Blackwell, 2008)
Native to South and Central America, many of the 700 species of suckermouth armored catfishes (Loricariidae, Siluriformes) are popular with aquarium hobbyists as algae-controlling ornamental fishes and are therefore bred, shipped and sold around the world. They are characterized by bony plates covering the body, a pair of subterminal barbels, sucking lips, usually a spine in front of the adipose fin, and a flat-bottom body shape (Page and Burr, 1991), and are naturally occurring in a variety of freshwater habitats from sea level to 3000 m, often surviving in conditions that exclude other fishes. Members of the genus Pterygoplichthys differ from most other loricariids by having a large dorsal fin with 10 or more dorsal fin rays, which gives them their common name sailfin catfish (Nico and Martin, 2001; Nelson et al., 2004; Page and Robins, 2006). Three species of Pterygoplichthys (Pterygoplichthys multiradiatus, Pterygoplichthys pardalis, and Pterygoplichthys disjunctivus) are closely related in that they lack an elevated supraoccipital process and have the supraoccipital bone posteriorly bordered by three scutes. Among these three species only P. multiradiatus (Hancock, 1898) has a pattern of uncoalesced dark spots on a light background (Page and Robins, 2006)